Optimasi Parameter 3D Printing Terhadap Keakuratan Dimensi dan Kekasaran Permukaan Produk Menggunakan Metode Taguchi Grey Relational Analysis - Andik Aris Setiawan; Bayu Wiro Karuniawan; Nurvita Arumsari (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
The process of 3D printing using FDM (Fused Deposition Modelling) technology have many disadvantages, which are per layer product building system, different material properties and undefined parameters that makes it difficult to produce an optimum product quality. Therefore, the user of FDM technology 3D printing machine must do a research to achieve the correct parameter to have the optimum quality. In order to have the optimum product quality a research of parameter using optimization method is required. In this research, an experiment of specimen printing using 3D FDM technology 3D printing machine is done, the material is PLA (polylatic acid) with various different combination of parameters. The experiment is done in accordance with the experiment design designed with Taguchi Grey Relational Analysis method, combining two responses in one process to achieve the optimum parameter. After the optimum parameter is predicted, a confirmation experiment is conducted to prove that the parameter is correct and optimum. The result of this research are parameters with level of (A)1, (B)2, and (C)1 which is (A) 20 mm/s printing speed, (B) 210o C printing temperature, and (C) layer height resulting in 99% average dimensional accuracy and average roughness value of 11 Âµm. Therefore, it is concluded that the best 3D printing parameter is that of low level